Genome-Wide Association Study for Body Weight and Carcass Weight in Sumba Ongole Bulls (Bos indicus) - Hartati; Putra, W. P. B. (Faculty of Animal Science, Bogor Agricultural University, 2023)
Sumba Ongole (Bos indicus) is a native beef cattle that adapts well in Sumba Island of Indonesia. This study was carried out to perform a genome-wide association study for body weight (BW) and carcass weight (CW) in Sumba Ongole (SO) bulls. A total of forty-eight (n=48) SO bulls were used in this study. The data were collected from the slaughterhouse at Bogor City, West Java, Indonesia, and were analyzed using a genomic software of TASSEL 5.0 to obtain the best genetic marker. The result showed that the threshold Manhattan plot (-Log10P3) was used to select SNP markers for BW and CW in SO bulls. The two (2) SNP markers at BTA1, i.e., ARS-BFGL-NGS-3162 (CEP63 gene) and ARS-BFGL-NGS-78232 were significantly associated with BW and CW, respectively. Nonetheless, the genetic diversity in both SNP markers was low, with a PIC value of less than 0.30. In conclusion, the heterozygous TG bulls in CEP63 gene have higher CW than homozygous TT bulls.